Sept nouveaux exemplaires de plaques-boucles mérovingiennes en matière dure animale - Yvon Lemoine; Isabelle Rodet-Belarbi; Sébastien Poignant; Vincent Marchaisseau; Jean-François Goret (Archéologie Médiévale)
Seven new buckles-plates, carved in animal bone or antler, have recently been found, both with and without their buckles. They have been located in Île-de-France, Champagne and in the South-East of France. Six were discovered in graves ; the seventh was found in a refuse dump. This article presents their study, highlighting a fairly uncommon artefact type.